Assessment of 26 elements in hair and internal tissues of Persian jird (Meriones persicus) in Darreh Zereshk copper mine, Iran. Issue 5 (3rd September 2022) - Khazaee, Manoochehr; Hamidian, Amir Hossein; Mirjalili, Seyyed Ali Ashghar; Ashrafi, Sohrab; Khazaee, Aria
ABSTRACT: This study evaluated the bioaccumulation of 26 elements in five tissues of Persian jird ( Meriones persicus ) captured from Darreh Zereshk copper mine. The elements' concentrations were found to be distributed differently among various tissues. A significant relationship was observed between hair and liver for K ( r = −0.52) as well as between hair and heart for Cu ( r = 0.69) and Mg ( r = 0.62). Levels of Cr ( r = −0.53), Ni ( r = −0.62), and Ti ( r = −0.61) in the hair were negatively correlated with the body weight of rodents. Given the lack of significant relationships between the levels of most elements in hair and internal tissues, our results highlighted that hair of Persian jirds is not a suitable proxy for assessment of elements in internal tissues.